Após a nacionalidade: história do romance e produção romanesca no Brasil e na América Latina - Pedro Dolabela Chagas (Estudos de Literatura Brasileira Contemporânea)
The essay debates the representation of local identity as a guiding theme of the novel, as well as of critique and literary history in Brazil and Latin-America. We comment the theses of Roberto Echevarría about the Latin-American novel, which place on a wider geographical frame the propositions by Flora Süssekind about the Brazilian novel. Echevarría’s and Süssekind’s propositions orient our reading of the deconstruction, made in the 1980s and 90s, of the “nationality paradigm”. We then suggest the exhaustion of that critical gesture, given the recent changes in the representation of local identity in Brazilian and Latin-American literature. We argue that such changes demand a new historiographical approach: as a strategy to reveal historical patterns that are still invisible, we defend an analytical focus on the singularities of individual works. Finally, the readings of some contemporary authors synthesize the propositions forwarded.